DISTRIBUTIVE JUSTICE AND THE EFFECT OF BENEFIT TYPES ON JOB PERFORMANCE WITHIN FEDERAL GLC IN SARAWAK, MALAYSIA - Ismail, Azman; Clara Ong, Guat Leng; Yeop Yunus, Nek Kamal (International Business Education Journal, 2009)
This study was conducted to measure the moderating effect of distributive justice in the relationship between benefit types and job performance. A survey research method was used to gather 150 usable questionnaires from employees who have served in Malaysian federal government linked companies in Sarawak (GLCOMPANY). Outcomes of testing a moderating model using a hierarchical regression analysis showed that (l) interaction between distributive justice and medical treatment had not increased job performance, and (2) interaction between distributive justice and official duty claims had increased job performance, and (3) interaction between distributive justice and promotions had increased job performance. This study demonstrates that distributive justice does act as a partial moderating variable in the benefit program models of the organizational sector sample. In addition, the implications of this study to theory and practice, methodological and conceptual limitations, and directions for future research are also discussed.